Factors associated with intraventricular hemorrhage in preterm infants at Hospital Regional Docente de Trujillo. December 2011 to December 2013 - Valdivieso, Glauco (2015)
Objective: To determine the factors associated with intraventricular hemorrhage in preterm newborns in "Hospital Regional Docente de Trujillo" in the period December 2011 to December 2013. Material and Methods: Analytical, retrospective case-control study was conducted. The population consisted of 108 patients: 54 preterm infants with intraventricular hemorrhage and 54 preterm infants without intraventricular hemorrhage. Results: Birth weight was found to be significant (x2: 6.438, p-value: 0.011) reaching the rank of most frequent weight less or equal to 1500. The sex of child proved to be a significant variable (x2: 6.366, p-value: 0.012) being mostly males. Gestational age was found to be a significant variable (x2: 10.394, p-value: 0.001) being the most common age less or equal to 32 Weeks. Birth type was not a significant factor (x2: 0.150, p-value: 0.699), but caesarean section was more frequent (OR: 0.861). The Apgar score at one minute and five minutes was not a significant variable. The use of hyperosmolar solutions was not found to be significant (x2: 0.228, p-value: 0.633, OR: 0.795). The use of mechanical ventilation was not a significant variable (x2: 1.662, p-value: 0.197, OR: 1.75). The use of cardiopulmonary resuscitation was not a significant variable (x2: 0.055, p-value: 0.814, OR: 0.895). The use of pulmonary surfactant was not a significant variable (x2: 0.892, p-value: 0.322, OR: 1.643). Conclusion: Factors associated with intraventricular hemorrhage are birth weight less than or equal to 1500 g, gestational age less than or equal to 32 weeks and male gender of the newborn, but the type of birth, Apgar score, the use of hyperosmolar solutions, using mechanical ventilation, requirement of CPR and use of pulmonary surfactant was not a risk factor. The degree of intraventricular hemorrhage in preterm infants was the Grade I according to the classification of Papile.